Introduction to the special issue "Cultural industries and transmedia in a time of convergence: Modes of engagement and participation". Issue 5 (19th October 2016) - Gordon, Ian; Lim, Sun Sun
ABSTRACT: Our special issue offers studies of specific instances of transmedia. On the one hand, one set of studies looks at the different strategies media corporations have adopted for engaging audiences. On the other hand, another set of studies looks at media users' negotiations of the transmedia landscape. The collection as a whole brings together perspectives from history, communication, media studies, linguistics, STS (science and technology studies), and philosophy.